Balanced scorecard como ferramenta de comunicação de estratégica: um estudo em instituição financeira - Barino, Bruno Costa (2010)
In order to be competitive in the global environment, the companies should perform all stages of the productive process with excellence, what leads to the necessity of having efficient management tools in place. In this context is introduced the Balanced Scorecard, positioned as a tool able to manage and connect all department within the company. The current work presented a research conducted in a global financial institution with operations in Brazil, which implemented the Balanced Scorecard since the management of the company up to each individual in all hierarchic levels, using the tool as a way to measure the individual performance and also to communicate the company s strategy. The goal of this work was evaluating BSC s potential as a tool to communicate the company s strategy across the different hierarchic levels presented in the company. Therefore, it was conducted a research with 196 employees in the institution, categorized by hierarchic level (management and operational/non management), in order to identify the evaluation towards the BSC contribution to the improvement of the company s overall performance and, specifically, regarding finance, clients process and people, the BSC s four dimensions. Supported statistical analysis like T Test, Linear Regression Model and Pearson Correlation, the research identified that the evaluation of the two groups regarding the tool is similar, both in terms of overall efficiency and also in terms of each BSC dimension separately. Based on this information, the research concluded that the BSC was aligned and implemented across the different hierarchic levels of the company in a uniform process, with a consistent performance evaluation for all employees involved. An interesting aspect that demands additional research is the employee s evaluation regarding the main impacts of the BSC in the company: according to the research results, both the employees in the operational levels and also in the management level identify the BSC as an efficient tool to align the strategy and develop new metrics to evaluate the company s performance, but on the other hand, they don t present a positive evaluation regarding BSC s direct impact in the improvement of the company s performance